2022
DOI: 10.1177/2050313x221100400
|View full text |Cite
|
Sign up to set email alerts
|

Midodrine to optimize heart failure therapy in patients with concurrent hypotension

Abstract: According to the Centers for Disease Control and Prevention statistics, about 6.2 million adults in the United States have heart failure. Guideline-Directed Medical Therapy (GDMT) involving the use of renin-angiotensin-aldosterone system inhibitors with or without a neprilysin inhibitor, β-blockers, mineralocorticoid-receptor-antagonists, and sodium-glucose cotransporter-2 inhibitors serve as the backbone for heart failure with reduced ejection fraction (HFrEF) therapy. However, in patients with refractory hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 15 publications
(19 reference statements)
0
1
0
Order By: Relevance
“…However, a poster presentation ( Scoma et al, 2021 ) indicated significantly higher all-cause mortality at 6 months following hospitalization in the midodrine group compared to the non-midodrine group (HR:6.7, 95% CI:5.2%–8.5%). There have been some recent case reports showing potential benefits (at least in terms of blood pressure improvement and a higher likelihood of GDMT) ( Hajjiah et al, 2022 ; Shiu et al, 2022 ). However, these studies were only case series with small sample sizes, lacking matched controls, and limited to short-term follow-ups.…”
Section: Introductionmentioning
confidence: 99%
“…However, a poster presentation ( Scoma et al, 2021 ) indicated significantly higher all-cause mortality at 6 months following hospitalization in the midodrine group compared to the non-midodrine group (HR:6.7, 95% CI:5.2%–8.5%). There have been some recent case reports showing potential benefits (at least in terms of blood pressure improvement and a higher likelihood of GDMT) ( Hajjiah et al, 2022 ; Shiu et al, 2022 ). However, these studies were only case series with small sample sizes, lacking matched controls, and limited to short-term follow-ups.…”
Section: Introductionmentioning
confidence: 99%
“…However we agree that hypotension could be the Achilles' heel for up titration of GDMT and differently from the real word practice, most trials have included patients without significant hypotension at baseline. In the last years, some Authors have described, in small case series, the off-label use of Midodrine in hypotensive HFrHF patients [9,10]. However from these small reports the role of Midodrine administration to allow initiation and optimization of GDMT remains unfortunately unproven as well as its safety.…”
mentioning
confidence: 99%